AI in Medicine: Advisor, Copilot, or Navigator? - Ahmad Guni; Hutan Ashrafian (Frontiers for Young Minds, 2026)
When you go to the doctor, you might expect a human expert to decide what is wrong and what treatment is needed. But today, computers are starting to help with some parts of medical care. Artificial intelligence (AI) can point out possible problems, help analyze test results, and sometimes even carry out a specific task on its own under carefully controlled conditions. In this article, we will explain how three basic levels of medical AI assistance—advisor, copilot, and navigator—can support doctors and patients. We also describe how AI systems learn from medical data and why human doctors will still play a central role in patient care. Although AI could help doctors work faster and spot disease earlier, these tools must be carefully tested and used in ways that support safe, trustworthy healthcare.